Incorporating Internal and External Training Load Measurements in Clinical Decision Making After ACL Reconstruction: A Clinical Commentary - Jeffrey B Taylor; Kevin R Ford; Robin M Queen; Elizabeth C Owen; Angela Spontelli Gisselman (International Journal of Sports Physical Therapy)
# Background and Purpose